HUBUNGAN TINGKAT PENDIDIKAN, TINGKAT SOSIAL EKONOMI DAN TINGKAT PENGETAHUAN ORANGTUA TENTANG PERAWATAN GIGI DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA BALITA DI DESA MANCASAN BAKI SUKOHARJO - Rahayu Setyaningsih; Irfan Prakoso (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background: Dental abnormalities are often found in preschool children is dentalcaries (cavities), since in general the state of children's oral hygiene is worse andmore children eating food and drinks that cause caries than adults. The role ofparents is indispensable in maintaining the health of children, especially dentaland oral hygiene for children of preschool age are still dependent on theirparents.The Purpose : to determine the relationship between the level of education,socioeconomic level and the level of parental knowledge about dental treatmentwith the incidence of dental caries in children under five yearâ€s in the villageMancasan.Subjects: The population in this study were all parents in Mancasan village whohave toddlers as many as 50 people.The sample in this studyused a sampling technique total sampling.Methods: This research is an analytical research design correlation to determinethe relationship between the level of education, socioeconomic level and the levelof parental knowledge about dental careResults: the results of multivariate statistical test values obtained Nagelkerke RSquare of 47.3%Conclusion: a variable level of education, socioeconomic level and the level ofknowledge together can influence the incidence of dental caries in children underfive years of 47.3% and the remaining 52.7% influenced by other variables.Keywords: Education level, social economy, the level of knowledge, DentalCaries